2013
DOI: 10.1017/s0967199413000233
|View full text |Cite
|
Sign up to set email alerts
|

Developmental potential of in vitro or in vivo matured oocytes

Abstract: This study compared the embryological features of mature and immature oocytes (different stages) collected from stimulated cycles of in vitro fertilization (IVF). Immature oocytes were identified, classified as PI (prophase I - germinal vesicle, GV) or MI (metaphase I), were matured in vitro and fertilized using the intra-cytoplasmic sperm injection (ICSI) technique. Fertilization potential, cleavage, and subsequent transfer/cryopreservation of the embryos derived from these in vitro matured oocytes were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The rates of usable embryos generated per oocyte (26%) and live-birth oocyte utilisation for GV− patients (5.7%) that we found were similar to rates of 31% and 5% found previously in much larger studies [15]. Furthermore, the proportions of MII and immature oocytes that we found,~85% and 15%, respectively, are also entirely consistent with published literature [7][8][9][10]. Collectively, this supports that although our study group was small, it was a representative population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rates of usable embryos generated per oocyte (26%) and live-birth oocyte utilisation for GV− patients (5.7%) that we found were similar to rates of 31% and 5% found previously in much larger studies [15]. Furthermore, the proportions of MII and immature oocytes that we found,~85% and 15%, respectively, are also entirely consistent with published literature [7][8][9][10]. Collectively, this supports that although our study group was small, it was a representative population.…”
Section: Discussionsupporting
confidence: 91%
“…Following hCG trigger during stimulated IVF cycles, typically around 70-85% of oocytes obtained at transvaginal oocyte retrieval (TVOR) are mature (MII-arrested) eggs with the other 15-30% being at MI-and GV− stages [7][8][9][10]. It is not known why some oocytes remain GV− arrested despite being exposed to an hCG stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…We found that an MI oocyte was 7.6 times more likely to have fertilization failure than an MII oocyte. A low normal fertilization rate of immature oocytes has been reported by other studies, and among MI oocytes, the fertilization rate was lower than that of in vitro-matured MI oocytes (Alcoba et al, 2015;De Vincentiis et al, 2013;Strassburger et al, 2004;Shu et al, 2007). The results of this study indicate that oocyte maturation has a direct influence on fertilization rates.…”
Section: Discussionsupporting
confidence: 45%
“…To be fertilized, oocytes should ideally reach maturity, as oocytes in PI and MI are too morphologically immature to be fertilized for the formation of good-quality embryos. MI-stage oocytes can spontaneously undergo in vitro meiotic maturation to MII-stage oocytes within a few hours after collection (Strassburger et al, 2004), but they generally remain unused because their rates of fertilization, blastocyst formation and implantation are lower than those of MII oocytes that mature in vivo (Strassburger et al, 2004;Alcoba et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…, 2010 ; Vieira et al. , 2011 ; Alcoba et al. , 2015 ) or on the use of IVM with intention-to-treat patients ( Bos-Mikich et al , 2011 ; Lucena & Moreno-Ortiz, 2013 ; Tominaga et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%